ZONAL LABELING OF VERTEX COMB PRODUCT OF GRAPHS - Amruddin, Mustaqim; Haning, Farly Oktriany; Putra, Ganesha Lapenangga; Pahnael, Jusrry Rosalina (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
Suppose there is a connected plane graph G with a set of vertex V (G) and a set of edges E(G) or G = (V,E). A zonal labeling of graph G is vertex labeling with the two nonzero elements of ring Z3 to vertex in graph G such that the sum of the label of the vertices on the boundary of every region of G is the zero elements in Z3. This labeling is zonal and graph G is zonal graph. This paper will discuss zonal labeling on a graph comb product with a graph zonal denoted G. The result states that Fy ⊵o G, T ⊵o G, U ⊵o G a is graph zonal and Wz ⊵o G is not a zonal graph.